Impact Echo Data Visualization through Augmented Reality - Kim, Seongah; Seo, Wonseok; Kim, Jinyoung; Kim, Sung Wook; Jeon, You Chang (Journal of Infrastructure Systems, 2022)
This study presents and discusses a comprehensive work of nondestructive evaluation of a concrete bridge deck using impact echo for delamination evaluation, including data collection, processing, and presentation. Among the typical process of most nondestructive evaluation methods, this paper focuses on data visualization through augmented reality (AR). The test was conducted on the concrete bridge deck constructed by the Korea Expressway Corporation Research Institute in South Korea. The tested bridge deck was made of latex modified concrete and presented several artificial defects. A two-dimensional delamination condition map was generated and displayed along with delamination depth on a smartphone screen through AR. The entire process of the developed system was run fully automated in real time. The developed system successfully demonstrated the potential of the AR visualization approach, which is an effective and intuitive aid for human inspection for infrastructure condition monitoring with respect to the delamination of a concrete bridge deck. The intuitive interaction with the outdoor road environment by AR-based nondestructive evaluation data visualization would contribute to efficient inspection and smooth communication between participated infrastructure maintenance teams.
Keywords: Augmented reality; Concrete bridge deck; Data collection; Data presentation; Echo data; Impact echo; Mobile applications; Non destructive evaluation; Non-destructive evaluation methods; Research institutes; Augmented reality (AR); Bridge deck; Concrete; Data visualization; Delamination; Impact echo; Mobile application; Nondestructive evaluation